Co-movement of foreign exchange rate returns and stock market returns in an emerging market: Evidence from the wavelet coherence approach - He, Xingxing; Gokmenoglu, Korhan K.; Kirikkaleli, Dervis; Rizvi, Syed Kumail Abbas (Wiley, 2023)
This study aims to investigate the causal relationship between the Turkish stock market returns, namely XU100, and foreign exchange rates, namely USD/TRY and EUR/TRY, in Turkey using the wavelet coherence approach. In this study, we focus on the period from April 2000 to March 2019. Our findings reveal the following: (i) While we identify substantial volatility in the exchange rate during the 2000 November (banking crisis), 2001 February (economic crisis), and 2018 July (exchange rate crisis) periods, significant volatility was observed in the Turkish stock market during the 2000 banking crisis, 2001 economic crisis, and 2008 global crisis periods; (ii) There is a negative correlation between the Turkish stock market and foreign exchange rates at different frequencies over the selected sample period; (iii) A unidirectional causality runs from the Turkish stock market to foreign exchange rates between 2000 and 2004 at a scale of 4 months and between 2008 and 2012 at a scale of 32 months; (iv) Although inconsistent results are observed for the models of USD/TRY-XU100 and EUR/TRY-XU100, our empirical results show that the correlations between USD/TRY and XU100 are stronger than between EUR/TRY and XU100.
Keywords: emerging market; exchange rate; stock market; Turkey; wavelet coherence